'For Those with Eyes to See': On the Hidden Meaning of the Animal Fable in the Rasāʾil Ikhwān al-Ṣafāʾ. (12th March 2018) - de Callataÿ, Godefroid
Abstract: Does the famous animal fable, as narrated by the Ikhwān al-Ṣafāʾ in Epistle 22 of their Rasāʾil, possess an inner meaning? The issue is not new, but it may be useful to address it again today, considering the recent, significant re-evaluation of the Epistles of the Brethren of Purity in the overall history of medieval thinking. It is also important to return to this issue since it was largely left aside by the editors of Epistle 22 who are part of the ongoing project by Oxford University and the Ismaili Institute to critically edit the entire collection of the Rasāʾil Ikhwān al-Ṣafāʾ . In the present article, I argue that the Ikhwān's animal fable does indeed contain an esoteric level of reading and that it must be understood in line with the Brethren's Ismaʿili or Ismaʿili-like aspirations but also, and more importantly, with their wish to take an approach as universal and syncretic as possible. The following motifs are discussed in detail: a) God's Intimates; b) Seventy / Seventy-Two; c) Seven; d) Yaʿsūb, Commander of the Bees; e) the Return of the Conjunction; f) Equator.